ALIRAN SESAT DALAM PERSPEKTIF HUKUM PIDANA ISLAM DAN HUKUM PIDANA NASIONAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
The disseminator and participant of deviants sects can be accused as an apostate or murtad. They have committed hudud crime or jarimah hudud and can be punished by death sentence or subsidiary sanction. Nevertheless, the sanctions cannot be implemented because Indonesia is not Islamic state. There is no law enforcement towards the participant of deviant sects. But, they are only requested to be mass repented. The argumentation is that the participants of deviants sects are only a victim, so the process of law enforcement must be adjusted to the leader or disseminator of deviant sects.